Effects of rainfall on thermal stratification and dissolved oxygen in a deep drinking water reservoir. Issue 15 (17th June 2020) - Liu, Miao; Zhang, Yunlin; Shi, Kun; Zhang, Yibo; Zhou, Yongqiang; Zhu, Mengyuan; Zhu, Guangwei; Wu, Zhixu; Liu, Mingliang
Abstract: Thermal stratification is crucial for water quality and ecological processes in deep lakes and reservoirs and can be substantially affected by meteorological and hydrological processes in the catchment. However, how thermal stratification responds to rainfalls of different intensities and changing hydrological processes has not been documented very well. Here, high frequency water column profiles at three stations in a large subtropical deep reservoir (Lake Qiandaohu, China) in 2017 were used to elucidate the impacts of rainfall on lake physical process and chemical environment. The impact of rainfalls on the thermal stratification and dissolved oxygen in riverine zone was more impressive than that in transitional and lacustrine zones. The effect on thermal stratification by rainfall was largely affected by the magnitude of rainfall. Moderate and heavy rainfall events could reduce the thermal stability of water column, deepen the mixing layer depth, and shape the thermocline, resulting from decrease of surface water temperature and increased inflows. While rainstorms could totally break up thermoclines in the riverine zone by high volume inflow flushing. In addition, we found that the hypoxia and anoxia initial depths increased during rainfall events in this reservoir, which were well related to the changes of mixing layer depths. This research highlights that quantifying the effects of rainfalls on thermal stratification and dissolved oxygen will be beneficial for optimizing reservoir management. Abstract : Rainfall events could reduce the thermal stability of water column, deepen the mixing layer depth, and shape the thermocline in the Lake Qiandaohu. Hypoxia and anoxia initial depth increased during rainfall events, which covaried with the mixing layer depth. The impacts of rainfalls on the thermal stratification and dissolved oxygen in riverine zone were more impressive than that in transitional and lacustrine zones.